2000
DOI: 10.1177/1420326x0000900313
|View full text |Cite
|
Sign up to set email alerts
|

Formaldehyde in Occupied and Unoccupied Caravans in Australia

Abstract: A study of 132 unoccupied and 60 occupied caravans was conducted to determine levels of formaldehyde and factors which may affect these levels. Repeat monitoring was carried out 6 months later in 50 of the occupied caravans. A questionnaire was also used to assess po tential factors associated with the recorded levels. Mean formaldehyde levels of 100 ppb in unoccupied caravans and 29 ppb in occupied caravans were recorded. A nega tive correlation was found between formaldehyde levels and the age of caravans. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Higher values are occasionally encountered, especially in dwellings with urea-formaldehyde foam insulation [55]. Although this is less used nowadays as a building material formaldehyde is often encountered indoors as a residual chemical from the manufacture of insulation boards [56,57]. Since formaldehyde has been shown to be carcinogenic in rats, much of the interest in its presence arises through fears that it may also be a human carcinogen.…”
Section: Volatile Organic Compounds (Vocs)mentioning
confidence: 99%
“…Higher values are occasionally encountered, especially in dwellings with urea-formaldehyde foam insulation [55]. Although this is less used nowadays as a building material formaldehyde is often encountered indoors as a residual chemical from the manufacture of insulation boards [56,57]. Since formaldehyde has been shown to be carcinogenic in rats, much of the interest in its presence arises through fears that it may also be a human carcinogen.…”
Section: Volatile Organic Compounds (Vocs)mentioning
confidence: 99%
“…However, it is always better to be too thorough than too simplistic. Dear Sir, I found the article 'Formaldehyde in Occupied and Unoccupied Caravans in Australia' to be an interesting exposure study and it provides useful information on formaldehyde exposure in caravans [ 1 ]. However, I must take exception with the reporting of the summary data and statistical analysis.…”
mentioning
confidence: 99%
“…However, for exposure data, it is suggested that the W test is most appropriate, particularly for sample populations with less than 50 measurements [2][3][4]. For exposure samples, including area samples as reported in the article [1], previous studies [3,7,10,11,17] have suggested the distribution to be nonnormal and to best fit a logarithmic function. When these data, the exposure samples, are transformed using logarithms, distribution would then appear normal.…”
mentioning
confidence: 99%